If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 18 = 12 + -9 Reorder the terms: 18 + 6x = 12 + -9 Combine like terms: 12 + -9 = 3 18 + 6x = 3 Solving 18 + 6x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 6x = 3 + -18 Combine like terms: 18 + -18 = 0 0 + 6x = 3 + -18 6x = 3 + -18 Combine like terms: 3 + -18 = -15 6x = -15 Divide each side by '6'. x = -2.5 Simplifying x = -2.5
| 142.5*91=20*x | | 8x+21=6x+69 | | 2x-4=7x-7-5x | | 142.5=20*91 | | 4x+35=14x+45 | | 0.7x=0.9+0.2x | | -4+2x=-8+24 | | 7y+10=2y+25 | | 4x+21=5x | | 1x+1y=400 | | 8.2x+24.88=-11.8x+24.10 | | 5x+3x=20x | | 11j+29+13j-12= | | (x-3)(x-4)(x-7)=0 | | (z+6)(z+6)=-4 | | 5ln(3x)-2=12 | | 6t-5=3t+6 | | (2u+3)(5+u)=0 | | 4x+2=-x+12 | | .70x+.35(120)=.35(96) | | 2z=i(2+9i) | | 2x^214=102 | | .25x+.15y=19 | | G=um | | P(X)=200-0.2x | | .4x+x=1250 | | (x-1)*dy=2x^3y*dx | | 2(x+3)-4=12 | | 12+4*x^3+12*x^2+123*x=0 | | 100-p=.8p-8 | | 4*x^3+12*x^2+123*x=0 | | 5x+7=43-4x |